Future projection of East Asian atmospheric rivers in high-resolution climate models - Yeeun Kwon; Seok-Woo Son (Weather and Climate Extremes)
Atmospheric rivers (ARs) play a critical role in extreme precipitation in East Asia during the East Asian summer monsoon. While ARs are projected to increase in a warming climate, their regional changes in East Asia remain unclear partly due to the use of relatively coarse models. This study investigates future changes in East Asian ARs using high-resolution climate model simulations. The results show a robust increase in AR frequency and associated precipitation in East Asia in the near future (2025–2050). ARs are also projected to become more intense and persistent with a considerable increase in extreme precipitation, although the quantitative change slightly differs depending on the AR detection algorithms. Such changes are primarily driven by thermodynamic processes, with dynamic processes playing a secondary role. However, the dynamic processes, especially low-frequency circulation changes, contribute significantly to the inter-model spread, determining the uncertainty in the future projections of East Asian ARs. This finding helps to better understand future changes in AR and associated extreme precipitation in East Asia.